Exploring Electrical Conductivity of Thiolated Micro‐ and Nanoparticles of Gallium - Shih-Hao Chiu; Mahroo Baharfar; Yuan Chi; Moonika Sari Widjajana; Zhenbang Cao; Francois-Marie Allioux; Jianbo Tang; Md. Arifur Rahim; Kourosh Kalantar-Zadeh (Advanced Intelligent Systems, 2023)
Nano‐/microparticles of gallium (Ga), as a low‐melting‐point metal, are extensively used in the fields of soft electronics and sensors to provide thermal and electrical conductivity. However, a passivating oxide layer can be formed on the surface of Ga nano‐/microparticles during the synthesis process. This oxide layer is removed by a secondary sintering step, especially mechanical sintering, which is generally not a controllable process, and compromises the integrity of the system. Herein, thiol molecules, 1‐butanethiol, thiophenol, and 4‐mercaptopyridine, that can functionalize the surface of Ga via sonication to reduce the oxidation of Ga surface are used. The resulting particles exhibit electrical conductivity based on metal–molecule junctions without the requirement for a sintering step. In particular, 4‐mercaptopyridine functionalized, thiolated Ga particles exhibit higher electrical conductivity compared to the other three thiolated Ga systems as the organic material conjugation provides conductive pathways for the mix. Subsequently, using these particle systems, soft devices are developed that can be used for gas, exhalation, and flex sensing. This study provides insights into the possibility of creating combinations of organic molecules with liquid metal‐based nano‐/microparticles to generate electrically conductive mixes and the prospects of fabricating multifunctional sensors.